Follow-up of CRT-D patients downgraded to CRT-P at the time of generator exchange - Frey, Simon Martin; Brenner, Roman; Theuns, Dominic A.; Al-Shoaibi, Naeem; Crawley, Richard J.; Ammann, Peter; Sticherling, Christian; Kühne, Michael; Osswald, Stefan; Schaer, Beat (Frontiers in Cardiovascular Medicine, 2023)
Background Some patients with cardiac resynchronisation therapy (CRT) experience super-response (LVEF improvements to ≥50%). At generator exchange (GE), downgrading (DG) from CRT-defibrillator (CRT-D) to CRT-pacemaker (CRT-P) could be an option for these patients on primary prevention ICD indication and no required ICD therapies. Long-term data on arrhythmic events in super-responders is scarce. Methods CRT-D patients with LVEF improvement to ≥50% at GE were identified in four large centres for retrospective analysis. Mortality, significant ventricular tachyarrhythmia and appropriate ICD-therapy were determined, and patient analysis was split into two groups (downgraded to CRT-P or not). Results Sixty-six patients (53% male, 26% coronary artery disease) on primary prevention were followed for a median of 129 months [IQR: 101–155] after implantation. 27 (41%) patients were downgraded to CRT-P at GE after a median of 68 [IQR: 58–98] months (LVEF 54% ± 4%). The other 39 (59%) continued with CRT-D therapy (LVEF 52% ± 6%). No cardiac death or significant arrhythmia occurred in the CRT-P group (median follow-up (FU) 38 months [IQR: 29–53]). Three appropriate ICD-therapies occurred in the CRT-D group [median FU 70 months (IQR: 39–97)]. Annualized event-rates after DG/GE were 1.5%/year and 1.0%/year in the CRT-D group and the whole cohort, respectively. Conclusions No significant tachyarrhythmia were detected in the patients downgraded to CRT-P during follow-up. However, three events were observed in the CRT-D group. Whilst downgrading CRT-D patients is an option, a small residual risk for arrhythmic events remains and decisions regarding downgrade should be made on a case-by-case basis.